Characteristics and role in outcome prediction of continuous EEG after status epilepticus: A prospective observational cohort. (7th May 2015) - Alvarez, Vincent; Drislane, Frank W.; Westover, M. Brandon; Dworetzky, Barbara A.; Lee, Jong Woo
Summary Objective Continuous electroencephalography (cEEG) is important for treatment guidance in status epilepticus (SE) management, but its role in clinical outcome prediction is unclear. Our aim is to determine which cEEG features give independent outcome information after correction for clinical predictor. Methods cEEG data of 120 consecutive adult patients with SE were prospectively collected in three academic medical centers using the 2012 American Clinical Neurophysiology Society's Standardized Critical Care EEG Terminology. Association between cEEG features and two clinical outcome measures (mortality and complete recovery) was assessed. Results In the first 24 h of EEG recording, 49 patients (40.8%) showed no periodic or rhythmic pattern, 45 (37.5%) had periodic discharges, 20 (16.7%) had rhythmic delta activity, and 6 (5%) had spike‐and‐wave discharges. Seizures were recorded in 68.3% of patients. After adjusting for known clinical predictive factors for mortality including the STatus Epilepticus Severity Score (STESS) and the presence of a potentially fatal etiology, the only EEG features (among rhythmic and periodic patterns, seizures, and background activity) that remained significantly associated with outcome were the absence of a posterior dominant rhythm (odds ratio [OR] 9.8; p = 0.033) for mortality and changes in stage II sleep pattern characteristics (OR 2.59 for each step up among these categories: absent, present and abnormal, present and normal; p = 0.002) for complete recovery. Significance After adjustment for relevant clinical findings, including SE severity and etiology, cEEG background information (posterior dominant rhythm and sleep patterns) is more predictive for clinical outcome after SE than are rhythmic and periodic patterns or seizures.